PENGENALAN ETIKA BERBAHASA INGGRIS UNTUK KELOMPOK SADAR WISATA DI DESA PANGSAN PETANG BADUNG UTARA - Sudipa I N; F. I M. Brata; I M. Rajeg; L. P. Laksminy (Buletin Udayana Mengabdi, 2012)
This community service was conducted in Pangsan Village, Petang, Badung Regency concerning with the Introduction of the Polite English for members of Tourism Awarness Group. The participants were 40 persons originally from 4 sub-village namely (a)Pangsan; (b) Sekarmukti; (c) Kasianan and (d) Pundung. The materials of this training are concerning with English vocabulary, conversation and other related ones for tourism among others : Hotel, Airport, Shopping, Vocation.The methods of training are respectively (a) Orientation; (b) Drill; (c) Feedback and (d) Continuation. Such methods seemed to be very effective for those who have been involving in tourism activities. The members could participate directly using the polite English and managed to cope with their own daily problems. The result of this training is relatively good. This can be proved by their ability to practice the topic in every end of the session combined with the written test at the last day.